Mastering Windows security and hardening : secure and protect your Windows environment from cyber threats using zero-trust security principles /: secure and protect your Windows environment from cyber threats using zero-trust security principles. (2022) - Dunkerley, Mark; Tumbarello, Matt
No abstract available